Unités paysagères fonctionnelles : outil d'aide à la planification territoriale - Pauline Delbosc; Attilius Ceccaldi; Christophe Panaïotis; Frédéric Bioret; Laëtitia Hugot (VertigO)
In the framework of the national program for the mapping of natural and semi-natural vegetation (CarHAB) and in the framework of CBNC on knowledge of vegetation, research is being carried out in Corsica to refine knowledge on the state and dynamic evolution of vegetation, to improve the analysis and monitoring of the state of conservation of Community interest habitats to satisfy the request of the Flora and Fauna Habitats Directive (FFHD), in order to better assess the impact of major development projects and to analyze ecological continuities. A hierarchical partition of the commune of Lama (Haute-Corse) was developed to relate land-use planning projects with vegetation dynamics. This partition is based on the typological and mapping definitions of physical and phytoecological models of Corsica correlated with the use patterns (human activities and landscaping, agrosylvopastoralism, urbanism ...). This approach has made it possible to define and prioritize the sectors with conservation challenges of the municipality but also to develop decision-making tools for territorial planning, in particular for the preparation of the future Local Planning Plan.